2007
DOI: 10.1111/j.1600-0668.2007.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ultraviolet photocatalytic oxidation for indoor air cleaning applications

Abstract: Implementation of air cleaning technologies for both VOCs and particles in office buildings may improve indoor air quality, or enable indoor air quality levels to be maintained with reduced outdoor air supply and concomitant energy savings. One promising air cleaning technology is ultraviolet photocatalytic oxidation (UVPCO) air cleaning. For the prototype device evaluated here with realistic mixtures of VOCs, conversion efficiencies typically exceeded the minimum required to counteract predicted VOC concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 29 publications
8
95
0
1
Order By: Relevance
“…In that range, the toluene conversion efficiency increased from ~ 30 to 90%, indicating that, under all the experimental conditions, the system did not achieve complete conversion. Previous studies showed that at such low toluene concentrations, the removal efficiency was shown to be independent of the initial concentration [13,15] which suggested low coverage of the catalyst surface and first-order dependence on toluene concentration. In our case, for a given flow rate, the removal efficiency observed at the longest reactor length (L = 10 cm) was significantly higher than that observed for L = 5 cm (Figure 3-A).…”
Section: Effect Of Air Flow Rate and Residence Time On Toluene Removalmentioning
confidence: 98%
See 2 more Smart Citations
“…In that range, the toluene conversion efficiency increased from ~ 30 to 90%, indicating that, under all the experimental conditions, the system did not achieve complete conversion. Previous studies showed that at such low toluene concentrations, the removal efficiency was shown to be independent of the initial concentration [13,15] which suggested low coverage of the catalyst surface and first-order dependence on toluene concentration. In our case, for a given flow rate, the removal efficiency observed at the longest reactor length (L = 10 cm) was significantly higher than that observed for L = 5 cm (Figure 3-A).…”
Section: Effect Of Air Flow Rate and Residence Time On Toluene Removalmentioning
confidence: 98%
“…Recently, a few studies investigated the removal performance of UVPCO at low VOC concentrations comparable to those encountered in buildings [11][12][13][14][15]. With VOC concentrations in the ppbv range, the low catalyst surface coverage led to different kinetics and mechanisms with respect to reactions using high gas phase concentrations (in the ppmv range), and the competition between different VOCs for reactive surface sites was shown to be insignificant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, photocatalytic 6 performance with ppbv-level VOC concentrations has also been reported (4,42). Here, we investigate the potential of these reactions at VOC concentrations that occur in buildings (in the low ppb range), by applying sampling and analytical techniques commonly used in indoor air quality characterization (43).…”
Section: Introductionmentioning
confidence: 99%
“…The application of heterogeneous photocatalytic oxidation (PCO) for air purification has been investigated intensively in the past two decades, particularly in converting indoor air volatile organic compounds (VOCs) into less toxic minerals, carbon dioxide and water (Zhao and Yang, 2003;Hodgson et al, 2007). This technique carries certain advantages such as: utilizing UV and/or visible light as initialization energy; non-selectivity of organic pollutants; potential to complete mineralization into CO 2 and H 2 O; and persistent effectiveness throughout the lifetime of the photocatalyst under ambient temperature.…”
Section: Introductionmentioning
confidence: 99%